Efficacy of Role Play Method Through Communication and Critical Thinking Approach in Arabic Reading Skills - Kiptiyana; Inayah, Inayah; Zun, Ellina Dwi Faning; Waemamu, Waesama-ae (Mantiqu Tayr: Journal of Arabic Language, 2026)
Arabic reading instruction in Indonesian secondary schools still faces major challenges due to the dominance of teacher centered and conventional learning practices that limit students’ engagement, communication, and critical thinking. In response to 21stcentury learning demands that emphasize communication and critical-thinking skills, this study proposes an integrative instructional model that combines the role play method with communicative and critical thinking approaches to enhance Arabic-reading skills. This study aims to determine the effectiveness of the role play method through a communicative and critical thinking approach on reading skills. This research is a quantitative approach with a quasi-experimental nonequivalent control group design. The participants were seventh grade students of Madrasah Tsanawiyyah Nahdlatul Ulama 19 Protomulyo Kaliwungu South selected through purposive sampling and divided into experiment and control classes. Data were collected through a reading comprehension test and analyzed using the Mann Whitney U test. The result indicated a significant difference in reading skill improvement between the two groups, with an Asymp. Sig. (2-tailed)= 0.000<0.05. This study contributes empirical evidence by repositioning reading from a passive activity into an interactive and analytical learning process through role play based instruction. The findings are expected to broaden the application of role play beyond productive skills and provide a practical pedagogical model aligned with 21stcentury competencies. Future research is recommended to examine this model in wider educational contexts, integrate digital learning tools, and conduct longitudinal and qualitative studies to explore its long-term impact on Arabic-reading development.